Kajian impact of emotional intelligence on monolingual and bilingual students’ academic achievement - Minaabad, Malahat Shabani; Rad, Monire Zahedi (Penerbit Universiti Kebangsaan Malaysia, 2016)
At the time of entering primary school, language merely a practical value for the child. The first language has a deep root in human being. However, there are children who learn two languages together in their language-learning ages and face no problems. The reason for this difference can be found in the level of these children’s intelligence, parents’ and friends’ attitudes, and also that of the child him/herself towards learning and using the second language. The present study has been started by collecting some questionnaires answered by 94 elementary school teachers. By analyzing the data obtained from questionnaires it has been concluded that the higher the rate of emotional intelligence is in students, the higher is their educational achievement rate and vice versa. Following the analysis in different aspects of emotional intelligence it is concluded that self-awareness aspect is significant in both monolinguals and bilinguals. Self-management aspect and relationship management is significant only in case of monolinguals. Consequently, training special teachers and taking the advantage of native teachers in bilingual regions, also the manner of increasing the emotional intelligence in students should be taught to elementary school teachers.